Subtropical estuarine carbon budget under various hydrologic extremes and implications on the lateral carbon exchange from tidal wetlands. (15th June 2022) - Yao, Hongming; Montagna, Paul A.; Wetz, Michael S.; Staryk, Cory J.; Hu, Xinping
Highlights: Estuarine carbon fluxes are highly dynamic from drought to hurricane-induced flood. Lateral exchanges from tidal wetlands dominate the total carbon loading. Annual CO2 emission from northwest Gulf of Mexico estuaries is double of the North American estuaries average. Interpretation of an estuarine carbon budget requires greater spatiotemporal coverage than past studies, and to meet the future climate change challenge. Abstract: As coastal areas become more vulnerable to climatic impacts, the need for understanding estuarine carbon budgets with sufficient spatiotemporal resolution arises. Under various hydrologic extremes ranging from drought to hurricane-induced flooding, a mass balance model was constructed for carbon fluxes and their variabilities in four estuaries along the northwestern Gulf of Mexico (nwGOM) coast over a four-year period (2014–2018). Loading of total organic carbon (TOC) and dissolved inorganic carbon (DIC) to estuaries included riverine discharge and lateral exchange from tidal wetlands. The lateral exchanges of TOC and DIC reached 4.5 ± 5.7 and 8.9 ± 1.4 mol·C·m −2 ·yr −1, accounting for 86.5% and 62.7% of total TOC and DIC inputs into these estuaries, respectively. A relatively high regional CO2 efflux (4.0 ± 0.7 mol·C·m −2 ·yr −1 ) was found, which was two times the average value in North American coastal estuaries reported in the literature. Oceanic export was the major pathway for losses of TOC (5.6 ± 1.7 mol·C·m −2 ·yr −1, 81.2% of total) and DIC (9.9 ± 2.9 mol·C·m −2 ·yr −1, 69.7% of total). The carbon budget exhibited high variability in response to hydrologic changes. For example, storm or hurricane induced flooding elevated CO2 efflux by 2–10 times in short periods of time. Flood following a drought also increased lateral TOC exchange (from -3.5 ± 4.7 to 67.8 ± 17.6 mmol·C·m −2 ·d −1 ) but decreased lateral DIC exchange (from 28.9 ± 3.5 to -7.1 ± 7.6 mmol·C·m −2 ·d −1 ). The large variability of carbon budgets highlights the importance of high-resolution spatiotemporal coverage under different hydrologic conditions, and the importance of carbon contribution from tidal wetlands to coastal carbon cycling.